TYPES OF EXPRESSIVE ACTS IN BOHEMIAN RHAPSODY MOVIE 2018 - Pijar Piscesco; Afriana (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
This descriptive qualitative study identified the expressive acts in Bohemian Rhapsody movie 2018. The theory from Martinez (2013) was utilized to examine the different types of expressive acts in the data source. Then, an observational approach and a non-participation technique were used to collect data for this research. The data was then evaluated using two methods. Those were pragmatic identity and pragmatic competence in equalizing. The researchers discovered 15 utterances that made by the characters in the movie Bohemian Rhapsody. Based on the character’s utterances, there were 5 different types of expressive acts. There were 2 acts that indicated the congratulating, 5 acts that indicated the thanking, 4 acts that indicated the apologizing, 1 act that indicated the condoling, and 3 acts that indicated the boasting. Furthermore, among the 15 utterances that had been discovered, the act of thanking became the most prominent among the other types of expressive acts.